Tinjauan Hukum Yuridis-Normatif Tukar Menukar Uang Tidak Tunai Penuh - Retnani, Almira Pambayun Adha; Masrukhin; Syahniar, Ariyani (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2025)
This study aims to find out the law regarding non-cash money exchange and how to avoid riba (usury) by carrying out alternative types of transactions. This research is a library study using a descriptive qualitative method with a normative legal approach. It examines and studies texts from Islamic law, such as the Qur'an, hadith, and the opinions of scholars that are relevant to the topic. After collecting the data, the information is processed and analyzed by summarizing and connecting theories related to the problem in order to draw conclusions. The results of the study show that paper money can be compared to gold and silver because it shares the same 'illah (legal reason), namely muṭlaq aṡ-ṡamaniyah (having value and serving as a means of exchange). Since the 'illah is not limited only to gold and silver, the rules of riba also apply to paper money, and zakat must be paid on it. In transactions exchanging the same type of money, such as rupiah for rupiah, the amounts must be equal, and the exchange must happen immediately. If there is a delay, either partially or fully, it will prevent the immediate transfer between the two parties, causing the transaction to fall into riba nasiah — a form of riba caused by delaying the delivery or acceptance of one of the exchanged riba items.Therefore, if such an exchange must happen, it is necessary to use an alternative form of transaction to avoid riba, such as a qardh (loan) contract or a qardh contract with collateral.